Corrigendum: Shallow Compaction Modeling and Upscaling: A One-Dimensional Analytical Solution and Upscaling - Zhang, Jingchen; Ma, Jingsheng; Couples, Gary D.; Osuji, Nicholas Izuchukwu (Frontiers in Earth Science, 2022)
Natural depositional processes frequently give rise to the heterogeneous multi-layer system, which is often overlooked but essential for simulation of a geological process. The sediments undergo the large-strain process in shallow depth and small-strain process in deep depth. With the transform matrix and Laplace transformation, a new method of solving multilayer small-strain (Terzaghi) and large-strain (Gibson) consolidations is proposed. Results from this work matches the numerical results and other analytical solutions well. According to the method of transform matrix which can consider the integral properties of multilayer consolidation, relevant upscaling method is developed. This method showed to be more effective than the normally-used weighted average method. Correspondingly, the upscaling results indicate that the upscaled properties of a multilayer system vary in consolidation process.